A case study on quality management system in construction project - Abdullah @ Mohd. Asmoni, Mat Naim (2005)
Lack of research on project-based Quality Management System (QMS) and slight improvement observed in managing quality at project level by those ISO 9000 certified construction related companies instigated this research. The objectives were to investigate the main elements of project-based QMS and to develop a projectbased QMS model that could be applied by all parties involved in construction project. The study commenced with the literature review which end-up with a set of propositions. The propositions then were scrutinised by the experts before they were explored during the case study. A single case study on the implementation of QMS at Kuala Lumpur International Airport (KLIA) project was conducted where data from multiple sources such as content analysis of the Project Quality Plan (PQP) and interview had been collected and analysed. The data from the multiple sources were triangulated and the main elements of project-based QMS were deduced. The main elements discovered for project-based QMS were management responsibility, quality planning, resources management, construction process control, inspection and testing, auditing, quality recording and data analysis and reporting. Using the IDEF0 modelling technique each element was converted into a context diagram. The result of a combination of all context diagrams formed a project-based QMS model for construction.